Issues of Introversion vs Extroversion in EFL classrooms - Ghoual, Benaouda (My University, 2018)
It is often misleading for teachers to identify and recognise their pupils’ personality types and create a reconcilable learning environment. Reflecting on this issue, our study attempts to investigate if English as Foreign Language (EFL henceforth) teachers have difficulties in distinguishing their pupils’ personality types or tend to mix between attitudes and personality types or mis-conceptualise them. The present study was conducted via following a triangular method: questionnaires (teachers’ and pupils’), an observation, and an experiment. Both qualitative and quantitative approaches are employed. The results demonstrate considerable facts concerning the ambiguity of pupils about the different criteria of each personality type. When being exposed to the strategies that were suggested for the selected teacher, pupils’ reactivity to the material being presented in the classroom was higher, but not as expected.
Case study: forth year middle school pupils at Baghdadi Benattia middle school, Sirat, Mostaganem
Keywords: Learning environment; Mis-conceptualisation; Personality types